Oxidative stress in liver of grass carp Ctenopharyngodon idella naturally infected with Saprolegnia parasitica and its influence on disease pathogenesis - Baldissera M.D. (2020)
© 2020, Springer-Verlag London Ltd., part of Springer Nature.Fungal diseases are one of the major problems in freshwater fish culture and have been linked to significant losses and high mortality rate, and saprolegniosis caused by Saprolegnia parasitica is the most important oomycete affecting freshwater fish worldwide. The hepatic pathophysiology of infection remains poorly understood and is limited only to histopathological alterations. Thus, the aim of this study was to evaluate whether tissue oxidative damage can be considered a pathway linked to liver damage during S. parasitica infection in grass carp (Ctenopharyngodon idella). Grass carp was divided into two groups (n = 12 per tank, in triplicate), as follows: uninfected group (without cotton-like tuft) used as control; and infected group (with presence of cotton-like tuft; naturally infected with S. parasitica). Hepatic reactive oxygen species (ROS) and lipid peroxidation (LPO) levels were higher in fish naturally infected by S. parasitica compared with uninfected fish, while no significant difference was observed regarding hepatic carbonyl protein levels. Hepatic antioxidant capacity against peroxyl radical (ACAP) levels, as well as superoxide dismutase (SOD), glutathione peroxidase (GPx), and glutathione S-transferase (GST) activities, was lower in fish naturally infected by S. parasitica compared with uninfected fish. No significant difference was observed between groups regarding glutathione reductase (GR) activity. Histopathological analyses of infected fish revealed generalized cytoplasmic necrosis, and condensation and pyknosis of the hepatocyte nucleus. Based on these evidences, S. parasitica infection elicits oxidative damage via (a) increased ROS production, (b) decreased ROS elimination, and (c) inhibition of enzymatic and non-enzymatic antioxidant defense system. In summary, a disease causes oxidative stress in fish naturally infected, and this oxidative disturbance may contribute directly speed up to disease pathogenesis.